Special aluminum alloy conductor rubber jacketed flexible cable for railway and preparation method thereof

By using styrene butadiene rubber and polyethylene resin matrix materials in the cable and adding specific functional additives and modified materials, the problems of insufficient wear resistance and sun exposure stability of existing cables are solved, and more efficient and stable product performance is achieved.

CN119798808APending Publication Date: 2025-04-11SHANDONG XINYI ALUMINUM ALLOY CABLE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510023519.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The wear resistance of existing cables is difficult to coordinate and improve during use, and cracking and falling off are prone to occur after exposure to the sun, which limits the efficiency of the product.

Method used

Styrene butadiene rubber and polyethylene resin are used as matrix materials, diisopropyl peroxide DCP, paraffin chloride, calcium stearate and silane coupling agent are added as functional additives, and the wear resistance and aging resistance of the cable are improved by the coordination of the addition of modified titanium dioxide and the strength modulator.

Benefits of technology

It significantly improves the wear resistance of the cable and the stability of the exposure to the sun and aging, ensuring the efficient and stable product during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005232079010000111
    Figure BDA0005232079010000111
Patent Text Reader

Abstract

The invention discloses an aluminum alloy conductor rubber jacketed flexible cable special for a railway. The cable comprises the following raw materials in parts by weight: 30-35 parts of butadiene styrene rubber, 15-20 parts of polyethylene resin, 2-5 parts of dicumyl peroxide (DCP), 4-7 parts of chlorinated paraffin, 3-5 parts of calcium stearate and 2-5 parts of a silane coupling agent. The butadiene styrene rubber and the polyethylene resin are adopted as base materials, dicumyl peroxide DCP, chlorinated paraffin, calcium stearate and the silane coupling agent are added to serve as functional auxiliaries, and modified titanium dioxide and the strength modifier are added to coordinate, cooperate and jointly achieve a synergistic effect, so that the wear resistance of the product is excellent, and the exposure anti-aging stability effect of the product is remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber sheathed flexible cables, and in particular to a special railway aluminum alloy conductor rubber sheathed flexible cable and a preparation method thereof. Background Art

[0002] Cable is a device for transmitting electric energy or signals. It usually consists of several or several groups of wires and has the characteristics of internal power supply and external insulation. Cables can be used to transmit electric (magnetic) energy and information and realize electromagnetic energy conversion. They are widely used in urban underground power grids, power station lead-out lines, internal power supply of industrial and mining enterprises, and underwater transmission lines across rivers and seas. There are many types of cables, including power cables, control cables, compensation cables, shielded cables, high-temperature cables, etc. They are composed of single or multiple wires and insulation layers, and are used to connect circuits and electrical appliances. However, the wear resistance of existing cables is difficult to coordinate and improve, and the products are prone to cracking and falling off after exposure to the sun, which limits the efficiency of product use. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a railway-specific aluminum alloy conductor rubber-sheathed flexible cable and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution:

[0005] The present invention provides a railway-specific aluminum alloy conductor rubber-sheathed flexible cable, the cable comprising the following raw materials in parts by weight:

[0006] 30-35 parts of styrene-butadiene rubber, 15-20 parts of polyethylene resin, 2-5 parts of dicumyl peroxide DCP, 4-7 parts of chlorinated paraffin, 3-5 parts of calcium stearate, and 2-5 parts of silane coupling agent.

[0007] The cable comprises the following raw materials in parts by weight:

[0008] 32.5 parts of styrene-butadiene rubber, 17.5 parts of polyethylene resin, 3.5 parts of dicumyl peroxide DCP, 5.5 parts of chlorinated paraffin, 4 parts of calcium stearate, and 3.5 parts of silane coupling agent.

[0009] Preferably, the silane coupling agent is silane coupling agent KH560.

[0010] Preferably, the cable further comprises 3 to 5 parts of modified titanium dioxide and 4 to 7 parts of strength modifier;

[0011] The modified titanium dioxide does not contain modified dopamine hydrochloride solution, nano calcium carbonate and sodium lignin sulfonate solution, and nano magnesium oxide and carboxymethyl cellulose. The performance of the products tends to deteriorate. The modified dopamine hydrochloride solution of the present invention has a significant improvement effect on the performance stability of the products.

[0012] The preparation method of modified titanium dioxide is:

[0013] S01: dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 are stirred and blended in a weight ratio of 4:2:1 to fully form a modified dopamine hydrochloride solution;

[0014] S02: Ultrasonic blending 1 to 3 parts of sodium lignin sulfonate solution, 2 to 5 parts of modified dopamine hydrochloride solution and 2 to 4 parts of nano calcium carbonate to obtain a blending system agent;

[0015] S03: 3-5 parts of the blending system agent, 1-3 parts of nano magnesium oxide and 2-4 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain modified titanium dioxide.

[0016] Preferably, the mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 4-7%.

[0017] Preferably, the rotation speed for sufficient stirring and blending is 450-550 r / min, and the stirring time is 20-30 min; the ultrasonic power for sufficient ultrasonic blending is 350-400 W, and the ultrasonic time is 10-15 min.

[0018] Preferably, the preparation method of the strength modifier is:

[0019] S101: The nano-attapulgite is first heat-treated at 150-170°C for 5-10 minutes, then heated to 300°C at a rate of 2-5°C / min, kept at that temperature for 2-5 minutes, and finally air-cooled to room temperature;

[0020] The nano-attapulgite, lanthanum chloride solution and sodium silicate solution are mixed in a weight ratio of 4:2:3 to obtain a nano-attapulgite liquid;

[0021] S102: treating the calcium sulfate whiskers with proton irradiation, and obtaining irradiated calcium sulfate whiskers after the irradiation is completed;

[0022] 3-5 parts of irradiated calcium sulfate whiskers, 1-3 parts of citric acid, 4-7 parts of nano-attapulgite liquid and 1-2 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strength modifier.

[0023] At the same time, the inventors of the present invention also found that the performance of the products deteriorated when no irradiated calcium sulfate whiskers were added to the strength modulator and no nano-attapulgite was added to the nano-attapulgite liquid. Only the product raw materials prepared by the method of the present invention had the most significant performance effect of the product. Other methods were not as obvious as the effect of the present invention.

[0024] Preferably, the proton irradiation treatment has an irradiation power of 350 to 400 W and an irradiation time of 20 to 30 min.

[0025] Preferably, the mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-6%.

[0026] The present invention also provides a method for preparing a railway-specific aluminum alloy conductor rubber-sheathed flexible cable, comprising the following steps:

[0027] The raw materials are weighed according to weight, and then melt-extruded by a twin-screw extruder to obtain a cable. The extrusion temperature is 175°C.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The product of the invention adopts styrene-butadiene rubber and polyethylene resin as base materials, adds dicumyl peroxide DCP, chlorinated paraffin, calcium stearate and silane coupling agent as functional additives, and adds modified titanium dioxide and strength modifier to coordinate and cooperate with each other, so that the product has excellent wear resistance and significant exposure and aging stability. The modified titanium dioxide adopts dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 to coordinate and cooperate, adds sodium lignin sulfonate solution and nano calcium carbonate to form a blending system, and then performs ball milling treatment on nano magnesium oxide and carboxymethyl cellulose. The modified titanium dioxide obtained by the coordination between the raw materials is used to enhance the coordination of system performance and improve the performance stability of the product; the strength modifier is made of nano-attapulgite, which is continuously thermally improved to optimize the interlayer spacing of the nano-attapulgite and improve the performance stability of the system. At the same time, lanthanum chloride solution and sodium silicate solution are used for coordination and then irradiated calcium sulfate whiskers, citric acid, nano-attapulgite liquid and carboxymethyl cellulose are blended and ball-milled. Through the coordination between the raw materials, the coordination effect of the strength modifier and the modified titanium dioxide is enhanced, thereby further improving the performance of the product. DETAILED DESCRIPTION

[0030] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] A railway-specific aluminum alloy conductor rubber-sheathed flexible cable, the cable comprising the following raw materials in parts by weight:

[0032] 30-35 parts of styrene-butadiene rubber, 15-20 parts of polyethylene resin, 2-5 parts of dicumyl peroxide DCP, 4-7 parts of chlorinated paraffin, 3-5 parts of calcium stearate, and 2-5 parts of silane coupling agent.

[0033] The cable comprises the following raw materials in parts by weight:

[0034] 32.5 parts of styrene-butadiene rubber, 17.5 parts of polyethylene resin, 3.5 parts of dicumyl peroxide DCP, 5.5 parts of chlorinated paraffin, 4 parts of calcium stearate, and 3.5 parts of silane coupling agent.

[0035] The silane coupling agent is silane coupling agent KH560.

[0036] The cable also includes 3 to 5 parts of modified titanium dioxide and 4 to 7 parts of strength modifier;

[0037] The preparation method of modified titanium dioxide is:

[0038] S01: dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 are stirred and blended in a weight ratio of 4:2:1 to fully form a modified dopamine hydrochloride solution;

[0039] S02: Ultrasonic blending 1 to 3 parts of sodium lignin sulfonate solution, 2 to 5 parts of modified dopamine hydrochloride solution and 2 to 4 parts of nano calcium carbonate to obtain a blending system agent;

[0040] S03: 3-5 parts of the blending system agent, 1-3 parts of nano magnesium oxide and 2-4 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain modified titanium dioxide.

[0041] The mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 4-7%.

[0042] The rotation speed for sufficient stirring and blending is 450-550 r / min, and the stirring time is 20-30 min; the ultrasonic power for sufficient ultrasonic blending is 350-400 W, and the ultrasonic time is 10-15 min.

[0043] The preparation method of the strength modifier is as follows:

[0044] S101: The nano-attapulgite is first heat-treated at 150-170°C for 5-10 minutes, then heated to 300°C at a rate of 2-5°C / min, kept at that temperature for 2-5 minutes, and finally air-cooled to room temperature;

[0045] The nano-attapulgite, lanthanum chloride solution and sodium silicate solution are mixed in a weight ratio of 4:2:3 to obtain a nano-attapulgite liquid;

[0046] S102: treating the calcium sulfate whiskers with proton irradiation, and obtaining irradiated calcium sulfate whiskers after the irradiation is completed;

[0047] 3-5 parts of irradiated calcium sulfate whiskers, 1-3 parts of citric acid, 4-7 parts of nano-attapulgite liquid and 1-2 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strength modifier.

[0048] The irradiation power of proton irradiation treatment is 350-400W, and the irradiation time is 20-30min.

[0049] The mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-6%.

[0050] A method for preparing a railway-specific aluminum alloy conductor rubber-sheathed flexible cable comprises the following steps:

[0051] The raw materials are weighed according to weight, and then melt-extruded by a twin-screw extruder to obtain a cable. The extrusion temperature is 175°C.

[0052] Example 1.

[0053] A railway-specific aluminum alloy conductor rubber-sheathed flexible cable, the cable comprising the following raw materials in parts by weight:

[0054] 30 parts of styrene-butadiene rubber, 15 parts of polyethylene resin, 2 parts of dicumyl peroxide DCP, 4 parts of chlorinated paraffin, 3 parts of calcium stearate, and 1 part of silane coupling agent.

[0055] The silane coupling agent is silane coupling agent KH560.

[0056] It also includes 3 parts of modified titanium dioxide and 4 parts of strength modifier;

[0057] The preparation method of modified titanium dioxide is:

[0058] S01: dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 are stirred and blended in a weight ratio of 4:2:1 to fully form a modified dopamine hydrochloride solution;

[0059] S02: Ultrasonic blending of 1 part of sodium lignin sulfonate solution, 2 parts of modified dopamine hydrochloride solution and 2 parts of nano calcium carbonate to obtain a blending system agent;

[0060] S03: 3 parts of the blending system agent, 1 part of nano magnesium oxide and 2 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain modified titanium dioxide.

[0061] The mass fraction of the dopamine hydrochloride solution is 2%; the mass fraction of the sodium lignin sulfonate solution is 4%.

[0062] The stirring and blending in this embodiment is performed at a rotation speed of 450 r / min, and the stirring time is 20 min; the ultrasonic power for the ultrasonic blending is 350 W, and the ultrasonic time is 10 min.

[0063] The preparation method of the strength modifier is as follows:

[0064] S101: The nano-attapulgite was first heat treated at 150°C for 5 min, then heated to 300°C at a rate of 2°C / min, kept at that temperature for 2 min, and finally air-cooled to room temperature;

[0065] The nano-attapulgite, lanthanum chloride solution and sodium silicate solution are mixed in a weight ratio of 4:2:3 to obtain a nano-attapulgite liquid;

[0066] S102: treating the calcium sulfate whiskers with proton irradiation, and obtaining irradiated calcium sulfate whiskers after the irradiation is completed;

[0067] 3 parts of irradiated calcium sulfate whiskers, 1 part of citric acid, 4 parts of nano-attapulgite liquid and 1 part of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strength modifier.

[0068] The irradiation power of proton irradiation treatment is 350W, and the irradiation time is 20min.

[0069] The mass fraction of the lanthanum chloride solution is 2%; the mass fraction of the sodium silicate solution is 3%.

[0070] The method for preparing a railway-specific aluminum alloy conductor rubber-sheathed flexible cable of the present embodiment comprises the following steps:

[0071] The raw materials are weighed according to weight, and then melt-extruded by a twin-screw extruder to obtain a cable. The extrusion temperature is 175°C.

[0072] Example 2.

[0073] A railway-specific aluminum alloy conductor rubber-sheathed flexible cable, the cable comprising the following raw materials in parts by weight:

[0074] 35 parts of styrene-butadiene rubber, 20 parts of polyethylene resin, 5 parts of dicumyl peroxide DCP, 7 parts of chlorinated paraffin, 5 parts of calcium stearate, and 5 parts of silane coupling agent.

[0075] The silane coupling agent is silane coupling agent KH560.

[0076] It also includes 5 parts of modified titanium dioxide and 7 parts of strength modifier;

[0077] The preparation method of modified titanium dioxide is:

[0078] S01: dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 are stirred and blended in a weight ratio of 4:2:1 to fully form a modified dopamine hydrochloride solution;

[0079] S02: Ultrasonic blending of 3 parts of sodium lignin sulfonate solution, 5 parts of modified dopamine hydrochloride solution and 4 parts of nano calcium carbonate to obtain a blending system agent;

[0080] S03: 5 parts of the blending system agent, 3 parts of nano magnesium oxide and 4 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain modified titanium dioxide.

[0081] The mass fraction of the dopamine hydrochloride solution is 5%; the mass fraction of the sodium lignin sulfonate solution is 7%.

[0082] The rotation speed for sufficient stirring and blending is 550r / min, and the stirring time is 30min; the ultrasonic power for sufficient ultrasonic blending is 400W, and the ultrasonic time is 15min.

[0083] The preparation method of the strength modifier is as follows:

[0084] S101: The nano-attapulgite was first heat treated at 170°C for 10 min, then heated to 300°C at a rate of 5°C / min, kept at that temperature for 5 min, and finally air-cooled to room temperature;

[0085] The nano-attapulgite, lanthanum chloride solution and sodium silicate solution are mixed in a weight ratio of 4:2:3 to obtain a nano-attapulgite liquid;

[0086] S102: treating the calcium sulfate whiskers with proton irradiation, and obtaining irradiated calcium sulfate whiskers after the irradiation is completed;

[0087] 5 parts of irradiated calcium sulfate whiskers, 3 parts of citric acid, 7 parts of nano-attapulgite liquid and 2 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strength modifier.

[0088] The irradiation power of proton irradiation treatment is 400W, and the irradiation time is 30min.

[0089] The mass fraction of the lanthanum chloride solution is 5%; the mass fraction of the sodium silicate solution is 6%.

[0090] A method for preparing a railway-specific aluminum alloy conductor rubber-sheathed flexible cable comprises the following steps:

[0091] The raw materials are weighed according to weight, and then melt-extruded by a twin-screw extruder to obtain a cable. The extrusion temperature is 175°C.

[0092] Example 3.

[0093] A railway-specific aluminum alloy conductor rubber-sheathed flexible cable, the cable comprising the following raw materials in parts by weight:

[0094] 32.5 parts of styrene-butadiene rubber, 17.5 parts of polyethylene resin, 3.5 parts of dicumyl peroxide DCP, 5.5 parts of chlorinated paraffin, 4 parts of calcium stearate, and 3.5 parts of silane coupling agent.

[0095] The silane coupling agent is silane coupling agent KH560.

[0096] It also includes 4 parts of modified titanium dioxide and 5.5 parts of strength modifier;

[0097] The preparation method of modified titanium dioxide is:

[0098] S01: dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 are stirred and blended in a weight ratio of 4:2:1 to fully form a modified dopamine hydrochloride solution;

[0099] S02: Ultrasonic blending of 2 parts of sodium lignin sulfonate solution, 3.5 parts of modified dopamine hydrochloride solution and 3 parts of nano calcium carbonate to obtain a blending system agent;

[0100] S03: 4 parts of the blending agent, 2 parts of nano magnesium oxide and 3 parts of carboxymethyl cellulose are blended and ball-milled at a speed of 1250 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain modified titanium dioxide.

[0101] The mass fraction of the dopamine hydrochloride solution is 3.5%; the mass fraction of the sodium lignin sulfonate solution is 5.57%.

[0102] The rotation speed for sufficient stirring and blending is 500 r / min, and the stirring time is 25 min; the ultrasonic power for sufficient ultrasonic blending is 375 W, and the ultrasonic time is 12.5 min.

[0103] The preparation method of the strength modifier is as follows:

[0104] S101: The nano-attapulgite was first heat treated at 160°C for 7.5 min, then heated to 300°C at a rate of 3.5°C / min, kept at that temperature for 3.5 min, and finally air-cooled to room temperature;

[0105] The nano-attapulgite, lanthanum chloride solution and sodium silicate solution are mixed in a weight ratio of 4:2:3 to obtain a nano-attapulgite liquid;

[0106] S102: treating the calcium sulfate whiskers with proton irradiation, and obtaining irradiated calcium sulfate whiskers after the irradiation is completed;

[0107] 4 parts of irradiated calcium sulfate whiskers, 2 parts of citric acid, 5.5 parts of nano-attapulgite liquid and 1.5 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1250 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strength modifier.

[0108] The irradiation power of the proton irradiation treatment was 375W, and the irradiation time was 25 minutes.

[0109] The mass fraction of the lanthanum chloride solution is 3.5%; the mass fraction of the sodium silicate solution is 4.5%.

[0110] A method for preparing a railway-specific aluminum alloy conductor rubber-sheathed flexible cable comprises the following steps:

[0111] The raw materials are weighed according to weight, and then melt-extruded by a twin-screw extruder to obtain a cable. The extrusion temperature is 175°C.

[0112] Example 4.

[0113] A railway-specific aluminum alloy conductor rubber-sheathed flexible cable, the cable comprising the following raw materials in parts by weight:

[0114] 32 parts of styrene-butadiene rubber, 16 parts of polyethylene resin, 3 parts of dicumyl peroxide DCP, 5 parts of chlorinated paraffin, 4 parts of calcium stearate, and 3 parts of silane coupling agent.

[0115] The silane coupling agent is silane coupling agent KH560.

[0116] It also includes 4 parts of modified titanium dioxide and 5 parts of strength modifier;

[0117] The preparation method of modified titanium dioxide is:

[0118] S01: dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 are stirred and blended in a weight ratio of 4:2:1 to fully form a modified dopamine hydrochloride solution;

[0119] S02: Ultrasonic blending of 2 parts of sodium lignin sulfonate solution, 3 parts of modified dopamine hydrochloride solution and 3 parts of nano calcium carbonate to obtain a blending system agent;

[0120] S03: 4 parts of the blending system agent, 2 parts of nano magnesium oxide and 3 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1100 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain modified titanium dioxide.

[0121] The mass fraction of the dopamine hydrochloride solution is 3%; the mass fraction of the sodium lignin sulfonate solution is 5%.

[0122] The rotation speed for sufficient stirring and blending is 60r / min, and the stirring time is 22min; the ultrasonic power for sufficient ultrasonic blending is 360W, and the ultrasonic time is 12min.

[0123] The preparation method of the strength modifier is as follows:

[0124] S101: The nano-attapulgite was first heat treated at 155°C for 6 min, then heated to 300°C at a rate of 3°C / min, kept at that temperature for 3 min, and finally air-cooled to room temperature;

[0125] The nano-attapulgite, lanthanum chloride solution and sodium silicate solution are mixed in a weight ratio of 4:2:3 to obtain a nano-attapulgite liquid;

[0126] S102: treating the calcium sulfate whiskers with proton irradiation, and obtaining irradiated calcium sulfate whiskers after the irradiation is completed;

[0127] 4 parts of irradiated calcium sulfate whiskers, 2 parts of citric acid, 5 parts of nano-attapulgite liquid and 1.2 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1200 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strength modifier.

[0128] The irradiation power of the proton irradiation treatment was 360W, and the irradiation time was 22 minutes.

[0129] The mass fraction of the lanthanum chloride solution is 3%; the mass fraction of the sodium silicate solution is 4%.

[0130] A method for preparing a railway-specific aluminum alloy conductor rubber-sheathed flexible cable comprises the following steps:

[0131] The raw materials are weighed according to weight, and then melt-extruded by a twin-screw extruder to obtain a cable. The extrusion temperature is 175°C.

[0132] Comparative Example 1.

[0133] The difference from Example 3 is that no modified titanium dioxide is added.

[0134] Comparative Example 2.

[0135] The difference from Example 3 is that no modified dopamine hydrochloride solution is added to the modified titanium dioxide.

[0136] Comparative Example 3.

[0137] The difference from Example 3 is that no nano calcium carbonate and sodium lignin sulfonate solution are added to the modified titanium dioxide.

[0138] Comparative Example 4.

[0139] The difference from Example 3 is that nano magnesium oxide and carboxymethyl cellulose are not added to the modified titanium dioxide.

[0140] Comparative Example 5.

[0141] The difference from Example 3 is that no strength modifier is added.

[0142] Comparative Example 6.

[0143] The difference from Example 3 is that no irradiated calcium sulfate whiskers are added to the strength modifier.

[0144] Comparative Example 7.

[0145] The difference from Example 3 is that no nano attapulgite is added to the nano attapulgite liquid.

[0146] The product performance tests of Test Examples 1 to 4 and Comparative Examples 1 to 7 were conducted, specifically testing the optical abrasion resistance of the products. The test results are as follows.

[0147]

[0148] The product of Example 3 has excellent wear resistance and excellent stability in the sun exposure environment. It can be seen from Comparative Examples 1 to 7 and Example 3 that the product does not add modified titanium dioxide or one of the strength modifiers, and the performance of the product deteriorates significantly. The coordinated combination of the two has the most obvious product performance effect, and the product performance can achieve coordinated improvement, and the product aging resistance stability effect is significant.

[0149] No modified dopamine hydrochloride solution is added to the modified titanium dioxide, no nano calcium carbonate and sodium lignin sulfonate solution are added to the modified titanium dioxide, and no nano magnesium oxide and carboxymethyl cellulose are added to the modified titanium dioxide; the modified dopamine hydrochloride solution of the present invention has a significant improvement effect on the performance stability of the product; the modified titanium dioxide adopts dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 to blend and coordinate, and sodium lignin sulfonate solution and nano calcium carbonate are added to form a blending system, and then nano magnesium oxide and carboxymethyl cellulose are blended and ball-milled, and the modified titanium dioxide obtained by blending and coordinating the raw materials and adopting the coordination between the raw materials enhances the coordination of system performance in the system and improves the performance stability of the product;

[0150] At the same time, when no irradiated calcium sulfate whiskers are added to the strength modifier and no nano-attapulgite is added to the nano-attapulgite liquid, the performance of the product is deteriorated. Only when the product raw material is prepared by the method of the present invention, the performance effect of the product is the most significant, and the effect of other methods is not as obvious as that of the present invention; irradiated calcium sulfate whiskers, citric acid, nano-attapulgite liquid and carboxymethyl cellulose are blended and ball-milled, and the coordination effect of the obtained strength modifier and modified titanium dioxide is enhanced through the blending and coordination between the raw materials, so that the performance of the product is further improved.

[0151] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0152] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A railway-specific aluminum alloy conductor rubber sheathed flexible cable, characterized in that: The cable comprises the following raw materials in parts by weight: 30-35 parts of styrene-butadiene rubber, 15-20 parts of polyethylene resin, 2-5 parts of dicumyl peroxide DCP, 4-7 parts of chlorinated paraffin, 3-5 parts of calcium stearate, and 2-5 parts of silane coupling agent.

2. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 1, characterized in that: The cable comprises the following raw materials in parts by weight: 32.5 parts of styrene-butadiene rubber, 17.5 parts of polyethylene resin, 3.5 parts of dicumyl peroxide DCP, 5.5 parts of chlorinated paraffin, 4 parts of calcium stearate, and 3.5 parts of silane coupling agent.

3. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 1, characterized in that: The silane coupling agent is silane coupling agent KH560.

4. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 1, characterized in that: The cable also includes 3 to 5 parts of modified titanium dioxide and 4 to 7 parts of strength modifier; The preparation method of modified titanium dioxide is: S01: dopamine hydrochloride solution, titanium dioxide and silane coupling agent KH550 are stirred and blended in a weight ratio of 4:2:1 to fully form a modified dopamine hydrochloride solution; S02: Ultrasonic blending 1 to 3 parts of sodium lignin sulfonate solution, 2 to 5 parts of modified dopamine hydrochloride solution and 2 to 4 parts of nano calcium carbonate to obtain a blending system agent; S03: 3-5 parts of the blending system agent, 1-3 parts of nano magnesium oxide and 2-4 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain modified titanium dioxide.

5. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 4, characterized in that: The mass fraction of the dopamine hydrochloride solution is 2-5%; the mass fraction of the sodium lignin sulfonate solution is 4-7%.

6. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 4, characterized in that: The rotation speed for sufficient stirring and blending is 450-550 r / min, and the stirring time is 20-30 min; the ultrasonic power for sufficient ultrasonic blending is 350-400 W, and the ultrasonic time is 10-15 min.

7. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 4, characterized in that: The preparation method of the strength modifier is as follows: S101: The nano-attapulgite is first heat-treated at 150-170°C for 5-10 minutes, then heated to 300°C at a rate of 2-5°C / min, kept at that temperature for 2-5 minutes, and finally air-cooled to room temperature; The nano-attapulgite, lanthanum chloride solution and sodium silicate solution are mixed in a weight ratio of 4:2:3 to obtain a nano-attapulgite liquid; S102: treating the calcium sulfate whiskers with proton irradiation, and obtaining irradiated calcium sulfate whiskers after the irradiation is completed; 3-5 parts of irradiated calcium sulfate whiskers, 1-3 parts of citric acid, 4-7 parts of nano-attapulgite liquid and 1-2 parts of carboxymethyl cellulose are blended and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is washed with water and dried to obtain a strength modifier.

8. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 7, characterized in that: The proton irradiation treatment has an irradiation power of 350-400W and an irradiation time of 20-30 minutes.

9. The railway-specific aluminum alloy conductor rubber sheathed flexible cable according to claim 7, characterized in that: The mass fraction of the lanthanum chloride solution is 2-5%; the mass fraction of the sodium silicate solution is 3-6%.

10. The method for preparing a railway-specific aluminum alloy conductor rubber-sheathed flexible cable as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: The raw materials are weighed according to weight, and then melt-extruded by a twin-screw extruder to obtain a cable. The extrusion temperature is 175°C.

Citation Information

Patent Citations

  • Middle-high voltage cable material and preparation method thereof

    CN106916381A

  • Resin abrasive disc and manufacturing method thereof

    CN118081640A

  • Wear-resistant scratch-resistant shading ABS (acrylonitrile-butadiene-styrene) material and preparation method thereof

    CN118325276A

  • New bandwidth network cable and preparation method thereof

    CN118791786A